Polymerization Techniques for Enhanced ZnS Nanostructure Performance in Industrial Settings - Roberts, Charlotte (Engineering International, 2020)
This study aims to optimize polymerization techniques for enhancing the performance of Zinc Sulfide (ZnS) nanostructures within polymer matrices for industrial applications. Despite the promising properties of ZnS nanostructures, their practical use is often limited by challenges related to nanoparticle dispersion and compatibility within polymers. To address this research gap, we systematically investigated in-situ, emulsion, and solution polymerization techniques. ZnS nanostructures were synthesized using a chemical precipitation method and characterized through XRD, SEM, and TEM to ensure high purity and controlled morphology. In-situ polymerization emerged as the most effective method, providing uniform dispersion and strong interfacial bonding. The optimized nanocomposites demonstrated significant improvements in mechanical strength, thermal stability, and electrical conductivity, confirmed by TGA, DSC, and UV-Vis spectroscopy. The findings underscore the critical role of tailored polymerization techniques in maximizing the industrial applicability of ZnS nanostructures. Policymakers and industry leaders can leverage these insights to develop high-performance materials for applications in electronics, coatings, and sensors, ultimately driving innovation and competitiveness in advanced manufacturing sectors.